Pengembangan Soal Higher Order Thinking Skill (HOTS) Fisika Kelas VIII SMP Materi Gerak Pada Benda (UPEJ Unnes Physics Education Journal, 2019)
Development research has been carried out to measure high-level thinking skills of junior high school students, through the development of HOTS questions of Physics in Middle School. This is based on the lack of students' skills in answering questions that require analysis, evaluation, and creativity, so that in learning activities they cannot answer questions that require high-level thinking skills. Sampling was done randomly and obtained three classes, namely class VIII D, E, F. Then the data was collected using HOTS questions that have been tested by experts. The analysis used in this study was to test the material validity by experts, the validity of the items, the distinguishing power, the level of difficulty, the reliability of the test, and the t-test. The results of this study are a set of instruments about the HOTS Physics Middle School subject matter on objects that can be used to measure students' high-level thinking abilities.